The appeal of internal review: law, administrative justice and the (non-) emergence of disputes - Cowan, David (Bloomsbury collections, 2003)
1 INTRODUCTION -- 2 HOMELESSNESS LAW AND INTERNAL REVIEW IN CONTEXT -- 3 SOUTHFIELD COUNCIL -- 4 BRISFORD COUNCIL -- 5 UNDERSTANDING THE FAILURE TO PURSUE INTERNAL REVIEW -- 6 UNDERSTANDING THE PURSUIT OF INTERNAL REVIEW -- 7 LAWYERS AND OTHER COPING STRATEGIES -- 8 CONCLUSION